Virtual Classroom in Teaching and Learning for Nursing Students in Digital Age - เจริญวงศ์ สิวาภรณ์; เกษโกมล ทิพย์ฆัมพร; ตามสัตย์ อภิสิทธิ์ (Journal of The Royal Thai Army Nurses, 2018)
The virtual classroom is an educational innovation in teaching and learning through a computer network or online system. This is a challenge for nursing instructors to apply the virtual classroom to the digital world. With the advancement of technology, students can access a wide range of learning resources, review and learn them all the time. That can lead them to develop their knowledge, awareness and professional skills. The important things that the instructors should consider the creation of the virtual classroom include selecting a topic or appropriate course content, meeting standards of the computer system, interfacing harmonious and user-friendly design, using easy-to-remember symbols, and uploading various, fun, and attractive multimedia. Moreover, it is comfortable to use. The space and style of the classroom are well suited to visibility and content classification is ordered respectively. Teaching and learning activities are appropriate for interaction. There are channels for searching or suggestions. A comprehensive assessment of learning outcomes should be measured with course objectives and learning outcomes. Encouraging students to learn in the virtual classroom with friends in pairs or in teams can help them to collaborate with others. However, the virtual classroom is just a tool or option to promote learning. It cannot substitute for actual nursing education because the nursing profession requires knowledge, attitude, skills, experience, spirit, and senses. Therefore, the virtual classroom cannot replace all.